Clinical and functional outcomes of cannabis use among individuals with anxiety disorders: A 3‐year population‐based longitudinal study. Issue 6 (27th February 2018) - Feingold, Daniel; Rehm, Jürgen; Factor, Hagai; Redler, Avigayil; Lev‐Ran, Shaul
Abstract : Background: Cannabis use has been reported to negatively affect the course and outcome of various psychiatric disorders, yet little is known on its effect on rates of remission from anxiety disorders and associated clinical and functional outcomes. Methods: In this study, data were drawn from Waves 1 and 2 of the National Epidemiologic survey on Alcohol and Related Conditions, focusing on individuals who qualified for a diagnosis of any anxiety disorder (social anxiety, panic disorder, generalized anxiety disorder, and specific phobias) at Wave 1 ( N = 3, 723). Cannabis users and individuals with cannabis use disorders (CUDs) throughout a 4‐year period were compared to nonusers in rates of remission, suicidality, general functioning, and quality of life at Wave 2, while controlling for baseline confounders. Results: Although rates of remission decreased with level of cannabis use, this was not maintained in adjusted models. Aside from specific outcomes (individuals with CUDs were significantly more prone to report breaking up from a romantic relationship; adjusted odds ratio [AOR] = 3.85, 95% confidence interval [CI] = 1.66–8.97) and repeatedly quitting school (AOR = 6.02, 95% CI = 2.65–13.66)), following adjustment no additional differences were found in outcome measures. Conclusions: These findings add to previous reports suggesting that poorer outcome of anxiety disorders among cannabis users may be attributed mainly to differences in baseline factors and not cannabis use.